2021
DOI: 10.1061/(asce)ir.1943-4774.0001561
|View full text |Cite|
|
Sign up to set email alerts
|

Sediment Movement over Type A Piano Key Weirs

Abstract: This investigation deals with the mechanics of movement of singular quartz gravel and coarse sand river bed particles in upstream and over inlet key of three type-A Piano key weir (PKW) models, which were recorded with a high-speed camera. Acoustic-Doppler-Velocimeter was used to obtain the upstream bed shear stress. The sediment threshold and regime over the upstream bed were compared with the previous investigations and found to be within the ranges. Generally, a sediment particle decelerates as it approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Denys and Basson (2020) showed that due to the formation of the recirculation zone, the upstream face of the rectangular PKW sidewall experiences significant pressure fluctuations (with an average amplitude of 10% of the total hydrostatic pressure) [37]. According to Kumar et al (2021), a sediment particle accelerates along the inlet key due to the flow contraction and an increase in shear stress [38]. Regardless of the limited ranges of the above-mentioned studies, they imply that the understanding of the complex flow structure (fundamental research) and the analysis of its possible relation to the discharge capacity (applied research) may clarify PKW benefits and limitations.…”
Section: H B B B W a A T C N S S P W P B B W D P R W (3)mentioning
confidence: 99%
“…Denys and Basson (2020) showed that due to the formation of the recirculation zone, the upstream face of the rectangular PKW sidewall experiences significant pressure fluctuations (with an average amplitude of 10% of the total hydrostatic pressure) [37]. According to Kumar et al (2021), a sediment particle accelerates along the inlet key due to the flow contraction and an increase in shear stress [38]. Regardless of the limited ranges of the above-mentioned studies, they imply that the understanding of the complex flow structure (fundamental research) and the analysis of its possible relation to the discharge capacity (applied research) may clarify PKW benefits and limitations.…”
Section: H B B B W a A T C N S S P W P B B W D P R W (3)mentioning
confidence: 99%
“…Zhao et al (2020) discovered that the saltation height and length increase if the particle shape is not spherical. Moreover, Kumar et al (2021) investigated sediment passage over type-A PKWs and observed that sediment passage at a lesser rate as it goes through the intake key and speeds up at the key entrance. Plunging and impinging jets originating from the inlet and outflow keys were credited with forming the ridge and dip (Kumar & Ahmad 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Bodaghi et al (2021) experimentally showed that by increasing tailwater depth and discharge, the scour depth downstream of a trapezoidal PKW decreases and increases under free flow conditions, respectively. Kumar et al (2021) investigated the movement of sediment particles on the inlet keys of a rectangular PKW under free-flow conditions. They observed that the speed of the sediment particles decreased by approaching the inlet key.…”
mentioning
confidence: 99%